2018
DOI: 10.7307/ptt.v30i2.2423
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Truck Weigh Stations’ Locations based on Truck Traffic Flow and Overweight Violation: A Case Study in Bosnia and Herzegovina

Abstract: The number of registered commercial freight vehicles is constantly increasing, increasing therefore as well the traffic load on the roads in Bosnia and Herzegovina. A significant part of freight vehicles moving along the main and regional roads are overloaded and cause significant damage to road infrastructure, affect road safety and result in an increase of emissions of harmful gases for people and the environment. The overloading rate is extremely high, in particular with 5-axle trucks representing 58.7%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There are several studies relevant to the determination of the real cost of transportation. Kulovic 23 established that transportation costs are a function of numerous factors such as different input prices, product characteristics, truck configuration, geographic characteristics, road conditions, and handling characteristics. These make the estimation of transportation costs difficult.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies relevant to the determination of the real cost of transportation. Kulovic 23 established that transportation costs are a function of numerous factors such as different input prices, product characteristics, truck configuration, geographic characteristics, road conditions, and handling characteristics. These make the estimation of transportation costs difficult.…”
Section: Methodsmentioning
confidence: 99%
“…The weight of the vehicle, including the goods, can be determined in several ways, which are based on different technologies. In principle, it is possible to determine the weight of vehicles at rest (stationary weighing) and while driving (dynamic weighing) [6,10,11]. During the roadside inspection, the police officer can check the weight of the vehicle and the securing of the goods.…”
Section: Road Technical Inspectionmentioning
confidence: 99%
“…The optimization of WIM stations location in the road network is the subject of consideration, e.g. in the works [14,29].…”
Section: Location Of the Stationmentioning
confidence: 99%
“…On the other hand, the report [13] states that in Slovenia the share of overloaded vehicles is 10.3% on motorways and 15.3% on national roads. In turn, the results of research conducted on the roads of Bosnia and Herzegovina indicate a 24.2% share of overloaded vehicles [14]. In the paper [15], it was indicated that the share of overloaded vehicles in Poland ranges from 6 to 16.5% depending on the location of the checkpoint.…”
Section: Introductionmentioning
confidence: 96%